Peculiarities of phase transformations in SiC crystals and thin films with in-grown original defects - Vlaskina, S.I.; Mishinova, G.N.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Phase transformations of SiC crystals and thin films with in-grown original defects have been studied. The analysis of absorption, excitation and low-temperature photoluminescence spectra testifies to formation of new micro-phases during the growth. The complex spectra can be decomposed into similar structure-constituting spectra shifted against each other on the energy scale. These spectra are indicative of formation of new nanophases. Taking into account the position of the short-wave edge in the zerophonon part of the SF-i spectra as well as the position of corresponding excitation spectra and placing them on the well-known linear dependence of the exciton gap (Egx) on the percentage of hexagonally in different polytypic structures, one can obtain a hint to the percentage of hexagonally in the new metastable structures appearing in the 6H (33) matrix or in the growth process. The SF spectra are indicative of the appearance of these metastable structures.